Association of the polymorphisms detected in B -lactoglobulin (B-LG) gene with milk production traits in Sirohi and Jamunapari breed of Indian goats - Satpal Dixit; Manoj Kumar Vyas; Sandeep Kumar; M K Singh; O.P. Pathodiya; Anurodh Sharma; S Jayakumar (Journal of Livestock Biodiversity, 2025)
The present investigation was carried out to explore the genetic polymorphisms in B -lactoglobulin (B-LG) gene and their possible association with milk production traits in two goat breeds of India. Total twelve SNPs were identified in caprine B -lactoglobulin (5’UTR, exon 1, exon 7 and 3’UTR) gene by screening 309 DNA samples of Jamunapari (140) and Sirohi (169) breed of goats using PCR - single strand conformation polymorphism (SSCP) and DNA sequencing. Out of twelve identified SNPs, four in 5’UTR (T1808C, C1866T, G2015T, C2084T and G2133A), one in intron 1(G3044A), one deletion at position 6591, two in exon 7 (G6751A, G6753C) and three in 3’UTR (T7011C, C7062A, G7147A) were detected. Association analysis revealed that the locus G2015T had significant effect on different milk production traits in Sirohi and Jamunapari goats. Locus T1808C and G6751A was found to be associated with milk yield in Jamunapari goats. The polymorphisms at the B -lactoglobulin associated with the milk production traits may be utilize as markers in selection of goats for high milk yield